Communication and cross-examination in court for children and adults with intellectual disabilities: A systematic review. (October 2019) - Morrison, Joanne; Forrester-Jones, Rachel; Bradshaw, Jill; Murphy, Glynis
Courts in England, Wales and Northern Ireland have identified children and adults with intellectual disabilities (ID) as vulnerable witnesses. The call from the English Court of Appeal is for advocates to adjust questioning during cross-examination according to individual needs. This review systematically examined previous empirical studies with the aim of delineating the particular communication needs of children and adults with ID during cross-examination. Studies utilising experimental methodology similar to examination/cross-examination processes, or which assessed the communication of actual cross-examinations in court were included. A range of communication challenges were highlighted, including: suggestibility to leading questions and negative feedback; acquiescence; accuracy; memory and understanding of court language. In addition, a number of influencing factors were identified, including: age; IQ level; question styles used. This review highlights the need for further research using cross-examination methodology and live practice, that take into consideration the impact on communication of the unique environment and situation of the cross-examination process.